SISTEM REGULASI DAN KEBIJAKAN PERPAJAKAN DI INDONESIA PERSPEKTIF EKONOMI ISLAM - Wartoyo Wartoyo (Nurul Jadid University, 2019)
Tax is a fiscal instrument in macroeconomic theory that can be used by the government to make funding (budgetary function) and regulation (regurelend function) in overcoming economic turmoil that always occurs in a country. The taxation system in Indonesia continues to change to adjust to the conditions and economic trends that occur in the world, so it is not surprising that there have been several tax reforms, including the birth of the Final PPH policy, Sunset Policy and Tax Amnesty. The goal is nothing but to adjust the needs of the rules to the real conditions that occur in the world economy and also in society so that state revenues from the tax sector can be fulfilled and in accordance with the targets mandated by the APBN. In Islamic economics itself tax is not something foreign, because it has been practiced since the beginning of Islamic rule where there were various kinds of taxes applied such as zakat, kharaj, khums, jizyah and so on. in the dialectic of taxes and alms there are two thoughts that arise, first is that which punishes taxes as zakat and second is that which still distinguishes the two. This difference has basically found a meeting point with the integration of zakat as a tax deduction that can be accepted by all levels of society in Indonesia.